Barbed suture pharyngoplasty in velopharyngeal complete concentric collapse: a multicentric study - Felipe Castillo-Farias; Marina Carrasco-Llatas; Gabriela Bosco; Vittorio Rinaldi; Peter Michael Baptista-Jardín; Giovanni Cammaroto; Uri Alkan; Noelia Muñoz-Fernandez; Pablo Rosel; Cristian Bachelet; Manuele Casale; Antonio Moffa; et al. (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Studies have shown that complete concentric circular collapse (CCC) at the velum is a frequent finding in drug-induced sleep endoscopy, implying a worse prognosis for surgical outcomes in the treatment of obstructive sleep apnea syndrome (OSAS). Our group evaluated the results of pharyngoplasties with barbed sutures for this indication. We selected 48 patients with OSAS and CCC who underwent pharyngoplasty with barbed sutures in 8 tertiary centers. The outcome results were measured by polygraphy or polysomnography and Epworth Symptoms Scale (ESS) at least 6 months after surgery. Results Apnea Hypopnea Index (AHI) improved from 34.9/h [21.2] to 12.7/h [10.6]. The success rate according to Sher’s criteria was 86.7%, the cure rate was 23.9%, and an AHI < 10 occurred in 42.2% of the cases. The oxygen desaturation index improved from 32.5/h [29.9] to 12.5/h SD [11.6], and the ESS improved from 10.2 [5.2] to 6 [3.5]. Conclusions Pharyngoplasty with barbed sutures seems to be a good alternative for patients with OSAS and CCC findings in drug-induced sleep endoscopy.